2019
DOI: 10.21468/scipostphys.6.6.078
|View full text |Cite
|
Sign up to set email alerts
|

Quantum robustness and phase transitions of the 3D Toric Code in a field

Abstract: We study the robustness of 3D intrinsic topogical order under external perturbations by investigating the paradigmatic microscopic model, the 3D toric code in an external magnetic field. Exact dualities as well as variational calculations reveal a ground-state phase diagram with first and second-order quantum phase transitions. The variational approach can be applied without further approximations only for certain field directions. In the general field case, an approximative scheme based on an expansion of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 91 publications
1
19
0
Order By: Relevance
“…In the past, this has been exploited successfully for two-and three-dimensional topological codes in a magnetic field in Refs. [63] and [8], respectively.…”
Section: B Variational Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past, this has been exploited successfully for two-and three-dimensional topological codes in a magnetic field in Refs. [63] and [8], respectively.…”
Section: B Variational Approachmentioning
confidence: 99%
“…Elementary excitations in two dimensions are so-called anyons [4,5] having a generalized particle statistics distinct from conventional bosons and fermions. Although anyonic point particles are forbidden in three spatial dimensions according to the spinstatistics theorem, the concept of fractional statistics can be generalized to spatially extended objects like membrane excitations in 3D [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in three-dimensional topologically-ordered systems point-like anyonic excitations are excluded but nontrivial statistics can be found for extended objects such as membranes. However, in 3D, one must distinguish between two main categories of topologically-ordered long-range entangled ground states [16,17] depending on whether their degeneracy is finite [18][19][20][21] or sub-extensive with the system size [22][23][24][25][26][27][28][29][30][31][32][33][34][35]. The topological order for systems with sub-extensive ground-state degeneracy is called fracton order.…”
Section: Introductionmentioning
confidence: 99%
“…Of the most interesting topological systems are topological quantum codes such as Toric code (TC) which has been introduced in context of quantum error correction [23]. It has been shown that nonlocal nature of such quantum codes leads to a natural robustness against local perturbations [24][25][26]. Beside the above practical applications, topological quantum codes can also be used as toy models for studying topological order because of their simplicity where topological phase transition out of a topological code state has attracted much attention [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%